2015
DOI: 10.1002/lary.25207
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects and clinical characteristics of familial meniere's disease in a South Korean population

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Our results are not similar to these results from Caucasian populations (Table ); the prevalence of familial MD and vestibular migraine are not higher in BMD than in patients with UMD. Recent studies with large European and Asian populations reported that the frequency of BMD was not higher in patients with familial MD than in those with sporadic MD . This observation suggests that several genes can affect the bilaterality of MD, but they may not be a main cause; de novo mutation/autoimmune pathologies can also elicit bilateral involvement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results are not similar to these results from Caucasian populations (Table ); the prevalence of familial MD and vestibular migraine are not higher in BMD than in patients with UMD. Recent studies with large European and Asian populations reported that the frequency of BMD was not higher in patients with familial MD than in those with sporadic MD . This observation suggests that several genes can affect the bilaterality of MD, but they may not be a main cause; de novo mutation/autoimmune pathologies can also elicit bilateral involvement.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, most studies concerning BMD have been based on the data from Caucasian populations, and reports from other ethnicities are lacking. Studies of BMD in a wider variety of countries and different ethnic populations are important because MD shows ethnic diversities in epidemiologic and genetic features …”
Section: Introductionmentioning
confidence: 99%
“…A sex difference has been reported in MD, with the ratio of women to men 1Á3 : 1 in Japan and 1Á89 : 1 in the United States [3,4]. Most cases were shown with an autosomal-dominant inheritance pattern [9,10]. Notably, it was estimated that definite familial MD might be found in 6Á3% of South Koreans and 8Á4% in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 Some of the described families presented co-segregation with migraine and anticipation, 12,25,26 but the two Spanish families that we report here do not show these features. Our study shows that AD-FMD has an incomplete penetrance with variable expressivity and it confirms a clinical heterogeneity in FMD.…”
Section: Discussionmentioning
confidence: 54%
“…13 Most of the cases of MD are considered sporadic, but familial clustering has been reported. 12,[14][15][16] Familial MD (FMD) is observed in 8-10% of sporadic cases, 17 and FAM136A and DTNA genes have been found in a single family with incomplete penetrance. 18 Although most cases present an autosomal dominant (AD) pattern of inheritance, different patterns have been observed, 14,15 suggesting a genetic heterogeneity in FMD.…”
Section: Introductionmentioning
confidence: 99%